Analysis of the Achievement of Indonesia's Nationally Determined Contribution Target in 2030 - Musa Partahi Marbun; Dandi Jiwo Lazuardi (ZETROEM, 2026)
Global climate diplomacy through the Paris Agreement obligates every member state to update their greenhouse gas (GHG) emission reduction commitments through the Nationally Determined Contribution (NDC) document. As a form of national implementation, the Government of Indonesia sets an emission reduction target in 2030 of 31.89% for the CM1 or unconditional scenario in the Enhanced NDC (ENDC) document. Furthermore, PT PLN (Persero) is mandated to contribute directly to GHG emission reductions by 127 Million Tons of CO2 in 2030 based on the unconditional scenario (CM1). However, along with the progress of GHG emission reduction achievements which have dynamics, there is a potential gap in achieving the GHG emission reduction target. Thus, an analysis of the fulfillment of the GHG emission reduction target by PT PLN (Persero) in 2030 is needed, as well as mapping the achievement prognosis and the challenges per mitigation activity. The use of a descriptive-analytical method based on literature study and review of regulatory documents of the Government of Indonesia and PT PLN (Persero), as well as emission reduction calculations, is carried out based on mathematical formulas that refer to the BAU scenario calculation in the ENDC. The analysis is focused on the comparison of three main data trends: the initial target of the ENDC document for the 2021–2030 period, the historical realization of emission reductions for the 2021–2025 period, and the prognosis of emission reductions for the 2026–2030 period across four main activities of PLN.